Analisis Desain UI/UX Pada Aplikasi Digital Signage Xibo Di Gedung Anti Corruption Learning Center (ACLC) Menggunakan Metode Heuristic Evaluation - Ari Siswanto; Anna Mukhayaroh (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bina Insani, 2025)
In an era of rapid advances in information technology, delivering information effectively and attractively has become a crucial element in various sectors, including education and public institutions. Digital signage comes as an innovative solution to answer these needs by providing a platform that allows the distribution of information visually and dynamically. One of the commonly used digital signage software is Xibo. In the Anti-Corruption Learning Center (ACLC) building, Xibo is used to display various information, such as announcements, activity schedules, and educational materials. But on the other hand, the UI/UX on the Xibo web has shortcomings, namely the non-intuitive design of the user interface which can cause users to feel confused and difficult in interacting with the website, which has the potential to affect user efficiency. To analyze the problems in the UI/UX of the Xibo web in depth, the author identifies usability standards in UI/UX design with the method used, namely Heuristic Evaluation. Based on the results of the analysis that has been carried out testing the level of usability that focuses on 10 aspects of heuristic evaluation of the Xibo digital Signage website shows that the website gets an average severy rating of 1. This value indicates that errors or deficiencies found on the website can still be tolerated by users, so they do not interfere with users when accessing it. Keywords: Xibo, Heuristic Evaluation, UI/UX, Severy Rating, Anti-Corruption Learning Center